International business - Faichuk, O. M.; Faichuk, O. V. (NULES of Ukraine, 2019)
The tutorial "International Business" is compiled in accordance with the work program of the course. Provides a systematic, logical explanation of the laws and objective principles of formation and development of the external and internal environment of international business at the beginning of the XXI century. Special attention is paid to the issues of internationalization of production, globalization and modern tendencies of development of multinational corporations, as well as strategies and organization of activities of international companies. The theoretically-structured material is harmoniously supplemented with practical tasks-cases, which should provide high interest in the study course. For students of higher education. It can also be useful for teachers, researchers, graduate students, heads of different levels of hierarchy of international companies, civil servants and those interested in contemporary problems of international business.
Recommended by the Academic Council National University of Life and Environmental Sciences of Ukraine
Keywords: business; International Business